2018
DOI: 10.1111/jgh.13986
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prucalopride on esophageal secondary peristalsis in reflux patients with ineffective motility

Abstract: Prucalopride enhances primary peristalsis and mechanosensitivity of secondary peristalsis with limited impact on secondary peristaltic activities in IEM patients. Our study suggests that prucalopride appears to be useful in augmenting secondary peristalsis in patients with IEM only via sensory modulation of esophageal secondary peristalsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 37 publications
1
36
0
1
Order By: Relevance
“…41,42 To the best of our knowledge, few studies have investigated esophageal motility during long-term acid reflux in individuals with CC and GERD. We found that most primary and secondary peristalsis is 26,47 Our study has several limitations. Less than expected high-extent reflux was detected, this discrepancy possibly being attributable to the high position of impedance loops (26 cm above the LES being defined as high extent in our study as compared with 15 cm above the LES being considered proximal, but not high-extent reflux in a previous study).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…41,42 To the best of our knowledge, few studies have investigated esophageal motility during long-term acid reflux in individuals with CC and GERD. We found that most primary and secondary peristalsis is 26,47 Our study has several limitations. Less than expected high-extent reflux was detected, this discrepancy possibly being attributable to the high position of impedance loops (26 cm above the LES being defined as high extent in our study as compared with 15 cm above the LES being considered proximal, but not high-extent reflux in a previous study).…”
Section: Discussionmentioning
confidence: 82%
“…The results of monitoring provided strong evidence that proton pump inhibitors (PPIs) are the optimal therapy for patients with GERD‐CC and cough caused by reflux, that is, adequate doses of more potent PPIs and prolonged treatment are indicated. As for reflux caused by cough, comprehensive antitussive measures might be more effective than overuse of PPIs whereas, if available, a prokinetic (ie, mosapride or prucalopride) may be indicated for patients with esophageal dysmotility (ie, IEM) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 A recent study also revealed that another 5-HT 4 receptor agonist, prucalopride, significantly increased pressure wave amplitude and the peristaltic success rate in patients with IEM. 20 A double-blind, randomized study in healthy volunteers reported that buspirone (5-HT 1A and 5-HT 2 receptor agonists), bethanechol, and pyridostigmine (a cholinesterase inhibitor) significantly enhanced mean DEA and mean LES residual pressure. 8 Therefore, it is presumed that prokinetic agents could be used to treat minor disorders of peristalsis by enhancing esophageal motility.…”
Section: Discussionmentioning
confidence: 99%